A produção do discurso da psicanálise em tempos de consumo - Gosmão, Reynaldo de Azevedo (2021)
This research sought to analyze the production of the discourse of psychoanalysis in times of consumption. With the general objective of analyzing the possible effects of meanings between the discourse of psychoanalysis and the discourse of consumerism through the categories of conditions of discourse production and the constitution of the subject within the psychoanalytic discourse at different historical moments. We seek to make this analysis through linguistic-discursive strategies of the positions of these subjects and the possible effects of meaning arising. Discourse Analysis is the theoretical and analytical apparatus of the project, through the concepts of interdiscourse, conditions of discourse production and subject. Thus, it is expected to raise the forms of representation of the discourse of consumerism and the discourse of psychoanalysis and also the place of the subject within these processes in a corpus that represents markers from different times of psychoanalysis in a socio-historical path. The corpus being the prefaces of the works: Studies on hysteria (1895-1990), written by Sigmund Freud and Josef Breuer, which will serve as a contrast and counterpoint to the analysis of the preface of the work: O mal, o bem e mais mais (2006 ), by Flávio Gikovate. The authors who reference this research are Dominique Maingueneau, Jean Jacques Courtine, Eni Orlandi and Erving Goffman. As a result of this analysis, we can understand that within the psychoanalysis discourse, the historization and the affiliations of the subjects to the ideological formations are a factor that directly interferes in the sliding of the senses of the psychoanalysis discourse, from a discourse close to the scientific discourse to the discourse of the psychoanalysis. consumerism, slips that integrate the CP of the discourse and that are responses to social effects of a given historical moment.